- #1

- 2

- 0

## Main Question or Discussion Point

suppose I have a function f(x) which I know increases as x.

I'm trying to combine a for loop and if statement

x(1)=a;

x(2)=b;

x(3)=(a+b)/2;

for i=3:n

if f(x(i)) > A

x(i+1) = (x(i-2)+x(i))/2;

else

x(i+1) = (x(i-1)+x(i))/2

end

end

this method works for x(4), the rest come with errors! Am I missing something obvious? Thanks.

I'm trying to combine a for loop and if statement

x(1)=a;

x(2)=b;

x(3)=(a+b)/2;

for i=3:n

if f(x(i)) > A

x(i+1) = (x(i-2)+x(i))/2;

else

x(i+1) = (x(i-1)+x(i))/2

end

end

this method works for x(4), the rest come with errors! Am I missing something obvious? Thanks.